Low‐order harmonic characteristics of photovoltaic inverters. (29th April 2015) - Shi, Qingxin; Hu, Haitao; Xu, Wilsun; Yong, Jing
Summary: The increasing penetration of photovoltaic (PV) systems, consisting of PV panel and PV inverter, may introduce power quality issues to the distribution power system. One critical concern is the harmonic distortion. This paper proposes an analytical harmonic model of PV inverters to assess its harmonic impacts on the distribution systems. The model is also verified by both simulation and laboratory experimental results. The proposed model indicates that the PV inverter has both harmonic source characteristic and harmonic impedance characteristic. Furthermore, the harmonic emission of PV inverters is affected by two grid operating conditions, namely the grid impedance and background harmonic voltage. The case studies demonstrate that the harmonic emission of a PV inverter without special harmonic control function can comply with the IEC standard under the normal grid operating conditions. It is verified that harmonic impacts of PVs are not a big concern. Copyright © 2015 John Wiley & Sons, Ltd.